Omega-conotoxin MVIIA reduces neuropathic pain after spinal cord injury by inhibiting N-type voltage-dependent calcium channels on spinal dorsal horn - Ohashi, Nobuko; Uta, Daisuke; Ohashi, Masayuki; Hoshino, Rintaro; Baba, Hiroshi (Frontiers in Neuroscience, 2024)
Spinal cord injury (SCI) leads to the development of neuropathic pain. Although a multitude of pathological processes contribute to SCI-induced pain, excessive intracellular calcium accumulation and voltage-gated calcium-channel upregulation play critical roles in SCI-induced pain. However, the role of calcium-channel blockers in SCI-induced pain is unknown. Omega-conotoxin MVIIA (MVIIA) is a calcium-channel blocker that selectively inhibits N-type voltage-dependent calcium channels and demonstrates neuroprotective effects. Therefore, we investigated spinal analgesic actions and cellular mechanisms underlying the analgesic effects of MVIIA in SCI. We used SCIinduced pain model rats and conducted behavioral tests, immunohistochemical analyses, and electrophysiological experiments (in vitro whole-cell patch-clamp recording and in vivo extracellular recording). A behavior study suggested intrathecal MVIIA administration in the acute phase after SCI induced analgesia for mechanical allodynia. Immunohistochemical experiments and in vivo extracellular recordings suggested that MVIIA induces analgesia in SCI-induced pain by directly inhibiting neuronal activity in the superficial spinal dorsal horn. In vitro whole-cell patch-clamp recording showed that MVIIA inhibits presynaptic N-type voltage-dependent calcium channels expressed on primary afferent Aδand C-fiber terminals and suppresses the presynaptic glutamate release from substantia gelatinosa in the spinal dorsal horn. In conclusion, MVIIA administration in the acute phase after SCI may induce analgesia in SCI-induced pain by inhibiting N-type voltagedependent calcium channels on Aδand C-fiber terminals in the spinal dorsal horn, resulting in decreased neuronal excitability enhanced by SCI-induced pain.